Narasumber Seminar: Pembelajaran Geografi dalam Peningkatan Pemahaman Mitigasi Bencana Banjir - Asep Asep (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Strengthening knowledge and disaster preparedness for students, teachers, and the wider community can be achieved through community service activities packaged in the form of national seminars. This seminar is an educational and collaborative forum that brings together various related parties to share knowledge, experiences, and disaster mitigation strategies. Through this community service activity, geography learning becomes more relevant and applicable. Not only does it increase understanding of disaster mitigation, this seminar also builds community capacity in dealing with disasters, and encourages active participation of all parties in creating a safer and more sustainable environment. This community service activity was carried out in three stages: 1) Material solidification, 2) Q&A discussion, 3) Evaluation. The community service conducted through a resource person at the national seminar on geography education organized by the Master of Geography Education Study Program at Padang State University provides an overview of the integration of processes and projects that can be done to improve understanding of disaster mitigation through geography learning. This includes projects such as identification of disaster locations in the selection of materials, socialization in collaboration with related parties, simulations in schools, or through the development of learning media.